Microplastics and the Placenta: A Call to Action for Perinatal Research - Kim, Jamie; Chen, Marcia; White, Robert S. (American Journal of Perinatology, 2025)
Microplastics have been detected in human placental and neural tissues, raising urgent concerns about their potential effects on maternal and fetal health. Emerging evidence links microplastics to systemic inflammation, neurotoxicity, and endocrine disruption, yet their impact on pregnancy outcomes and fetal development remains poorly understood. Given the placenta's central role in early-life health, perinatal researchers are uniquely positioned to lead investigations into this environmental threat. We call for collaborative, multidisciplinary research to better understand and mitigate the effects of microplastic exposure during pregnancy.
Keywords: microplastics; perinatal research; placenta; fetal health; maternal health